Heart‐centered positioning and tailored beam‐shaping filtration for reduced radiation dose in coronary artery calcium imaging: A Multi‐Ethnic Study of Atherosclerosis (MESA) Study. Issue 9 (3rd August 2021) - Colvert, Brendan; Rigolli, Marzia; Craine, Amanda; Criqui, Michael; Contijoch, Francisco
Abstract: Purpose: Cardiac computed tomography has a clear clinical role in the evaluation of coronary artery disease and assessment of coronary artery calcium (CAC) but the use of ionizing radiation limits the clinical use. Beam‐shaping "bow‐tie" filters determine the radiation dose and the effective scan field‐of‐view diameter (SFOV) by delivering higher X‐ray fluence to a region centered at the isocenter. A method for positioning the heart near the isocenter could enable reduced SFOV imaging and reduce dose in cardiac scans. However, a predictive approach to center the heart, the extent to which heart centering can reduce the SFOV, and the associated dose reductions have not been assessed. The purpose of this study is to build a heart‐centered patient positioning model, to test whether it reduces the SFOV required for accurate CAC scoring, and to quantify the associated reduction in radiation dose. Methods: The location of 38, 184 calcium lesions (3151 studies) in the Multi‐Ethnic Study of Atherosclerosis was utilized to build a predictive heart‐centered positioning model and compare the impact of SFOV on CAC scoring accuracy in heart‐centered and conventional body‐centered scanning. Then, the positioning model was applied retrospectively to an independent, contemporary cohort of 118 individuals (81 with CAC > 0) at our institution to validate the model's ability to maintain CAC accuracy while reducing the SFOV. In these patients, the reduction in dose associated with a reduced SFOV beam‐shaping filter was quantified. Results: Heart centering reduced the SFOV diameter 25.7% relative to body centering while maintaining high CAC scoring accuracy (0.82% risk reclassification rate). In our validation cohort, imaging at this reduced SFOV with heart‐centered positioning and tailored beam‐shaping filtration led to a 26.9% median dose reduction (25–75th percentile: 21.6%–29.8%) without any calcium risk reclassification. Conclusions: Heart‐centered patient positioning enables a significant radiation dose reduction while maintaining CAC accuracy.